Geographie als moderne theorieorientierte Sozialwissenschaft? - Wirth, Eugen (ERDKUNDE, 1984)
Led by Dietrich Bartels a dynamic group, made up argely of younger German geographers, has since1968 demanded that Human Geography should be conducted in line with a methodologically modern, theory-orientated social science. On the model of spatial analysis and the regional science of English-language geography all geographical research ought to aim itself at universally valid laws and comprehensive theories of social science. Where German geography has followed this summons it has for some years already been drawn into the serious crisis of modern social sciences. As a consequence, most recent epistemological developments of Human Geography in Germany can be summarized under three headings: 1. Thirty years of every-day research routine in the empirical social sciences have shown that a strict orientation towards the general, towards laws and comprehensive theories lead into a cul-de sac. It is often the case that not only the interesting nuances, but rather the essential and the decisive are submerged in the noise of the applied procedures. For that reason not only do many prominent social scientists turn to other concepts, but many geographers increasingly direct themselves towards the unique and the special. 2. The attempt by Hans Albert and Ernst Topitsch - two German social scientists - to transfer the principles of positivism in the theory of science from the natural sciences to the social sciences, must now be regarded as having failed. According to this concept, explanation in all sciences means a deviation from theories or theory like general statements. However, human activities can only be defined very imperfectly with the help of general theories; as a consequence, the search for suitable theoretical concepts has so far been in vain. 3. Equally unsuccessful was the theory of science's fundamental positivist conception that, in the social sciences, a fact is considered as explained when, and only when, its causes have been demonstrated. An explanation of human activity does not ask why, but what for. Thus it is not a matter of causes, but of intentions, motives, purposes, meaningful connections, orientations. Motivations, understanding, interpretation and creative explanation must take the place of causal explanation. In a research concept that promises to be highly successful in geography, human activity can be accounte for by rational recon struction of the respective particular action situation and of action strategies in retrospective analysis. In conclusion, by using examples it is shown how such a rational reconstruction of human activities can be carried out in geography.